Introduction (Itinera, 2022)
Colour reflects the “fluid” nature of the image: both can be considered as a factual, objective evidence of the external world as well as a subjective and sometimes deceptive re-representation of it.The section entitled “Colour. Photography, Image, Reality” collects essays that widely investigate the power of colour to unfold new sensibilities and practices linked the fruition, the creation and the use of images, across very different media: from literature to social media. The authors develop some core themes, such as the aesthetics of colors, the relevance of intermediality to comprehend specific experiences, and the epistemological and political implications of color technology.The reflections on images encounter the philosophical debate on colour, offering the opportunity to examine every pattern of recognition (that can be ours or of others, human or non-human) and contributing to the discussion on the contingent and questioning relationship between image and reality.